Influence of Calcination Conditions on Physical-Chemical Properties of Simulated High-Level Liquid Waste Calcinate - HE Cheng;ZHANG Hua;LI Zheng;WANG Run-ci (He huaxue yu fangshe huaxue, 2021)
Simulated high-level liquid waste is easy to stick to the furnace during the transformation process, which will affect its timely transport. In order to achieve a smoothly connection between the transformation process and the vitrification process, it is necessary to reduce the wall-sticking phenomenon by controlling the process conditions. At the same time, the changes of condition will lead to the changes in physical-chemical properties of the calcinate. In this paper, the simulated high-level liquid waste from the reprocessing of 45 GWd/tU spent fuel was used to study the physical-chemical properties such as particle size-distribution, moisture content, tap density and denitration efficiency under different temperatures and different rotation speeds. The particle size of calcinate is more uniform while increasing the temperature. When the rotation speed is between 15 to 20 r/min during 600 to 700 ℃, the moisture content of the calcinate is less than 2%, the tap density is about 1.7 g/cm3, and the denitration efficiency is more than 99%. Thus the calcinate can come out of the furnace successfully during the transformation process.